Evidence for the integration of total and free testosterone levels in the management of prostate cancer. (19th November 2021) - Huynh, Linda My; Huang, Erica; Towe, Maxwell; Liang, Karren; el Khatib, Farouk M.; Yafi, Faysal A.; Ahlering, Thomas E.
Abstract : Objective: To comprehensively assess total and calculated free testosterone levels in a consecutive group of patients with prostate cancer (PCa) and any potential impact on disease aggressiveness and recurrence outcomes. Participants and Methods: The study included a single‐centre prospective cohort of 882 patients presenting for radical prostatectomy from 2009 to 2018. Data on total testosterone (TT), sex hormone‐binding globulin (SHBG), and calculated free testosterone (cFT) were prospectively collected. Stepwise logistic regression models were used to assess correlations of TT and cFT with pathological Gleason Grade Group (GGG), extraprostatic extension (EPE), seminal vesicle invasion (SVI) and biochemical recurrence (BCR). Results: Total testosterone remained nearly constant across decades (40s–80s): 0.09 decrease/year ( R = 0.02), while SHBG increased 0.87/year ( R = 0.32) and cFT decreased 0.08/year ( R = −0.02). Low cFT of <5.5 independently predicted: very‐high‐risk GGG (odds ratio [OR] 0.435, 95% confidence interval [CI] 0.846–0.994; P = 0.036), EPE (OR 0.557, 95% CI 0.810–0.987; P = 0.011), SVI (OR 0.396, 95% CI 0.798–1.038; P = 0.059), and BCR within 1 year after robot‐assisted radical prostatectomy (OR 0.638, 95% CI 0.971–3.512, P = 0.046). TT was not a predictor. Conclusion: In contrast to popular belief, testosterone remained stable in men aged 40–80 years, whereas free testosterone decreased by 2–3%/year. Low cFT was an independent predictor of very‐high‐risk PCa and BCR.